Unraveling the Complexities of Immune Checkpoint Inhibitors in Hepatocellular Carcinoma - Han, Xinpu; Sun, Qianhui; Xu, Manman; Zhu, Guanghui; Gao, Ruike; Ni, Baoyi; Li, Jie (Seminars in Liver Disease, 2023)
Immune checkpoint inhibitors (ICIs) have emerged as effective therapeutics for multiple cancers. Nevertheless, as immunotherapeutic approaches are being extensively utilized, substantial hurdles have arisen for clinicians. These include countering ICIs resistance and ensuring precise efficacy assessments of these drugs, especially in the context of hepatocellular carcinoma (HCC). This review attempts to offer a holistic overview of the latest insights into the ICIs resistance mechanisms in HCC, the molecular underpinnings, and immune response. The intent is to inspire the development of efficacious combination strategies. This review also examines the unconventional response patterns, namely pseudoprogression (PsP) and hyperprogression (HPD). The prompt and rigorous evaluation of these treatment efficacies has emerged as a crucial imperative. Multiple clinical, radiological, and biomarker tests have been advanced to meticulously assess tumor response. Despite progress, precise mechanisms of action and predictive biomarkers remain elusive. This necessitates further investigation through prospective cohort studies in the impending future.
Keywords: immunotherapy; pseudoprogression; hyperprogression; resistance; hepatocellular carcinoma